Danggui Sini decoction for treating diabetic peripheral neuropathy: A protocol of systematic review and meta-analysis of randomized controlled trials - Zhang, Xiyu (Medicine (Baltimore), 2020)
BACKGROUND: Diabetic peripheral neuropathy (DPN) is one of the most common chronic complications of diabetic patients, which seriously affects the quality of life of patients. At present, mainstream drugs have problems such as poor efficacy and side effects. Traditional Chinese medicine (TCM) has extensive clinical experience in the prevention and treatment of diabetes and chronic complications, and it also shows clear advantages in the treatment of DPN. Clinical studies have confirmed that Danggui Sini decoction (DSD), a TCM decoction, can improve the clinical symptoms and signs of DPN patients. Therefore, we will conduct a systematic review to clarify the effectiveness and safety of DSD for DPN. METHODS: We will search every database from the built-in to October 2020. Chinese literature comes from CNKI, Wanfang, VIP, and CBM databases. English literature mainly searches Cochrane Library, PubMed, Web of Science, and EMBASE. At the same time, we will also search for clinical registration tests and gray literatures. This study only screened clinical randomized controlled trials (RCT) for DSD for DPN. The two researchers independently conducted literature selection, data extraction and quality assessment. Dichotomous data is represented by relative risk (RR), continuous data is represented by mean difference (MD) or standard mean deviation (SMD), and the final data is fixed effect model (FEM) or random effect model (REM), depending on whether it exists Heterogeneity. The main result is clinical efficacy and nerve conduction velocity. Fasting blood glucose, 2 hours postprandial blood glucose, blood lipid, hemorheology, and adverse events are secondary results. Finally, a meta-analysis was conducted through Review Manager software version 5.3. RESULTS: This study will conduct a comprehensive analysis based on the currently released DSD data for the treatment of DPN and provide high-quality evidence of clinical efficacy and safety. CONCLUSION: This systematic review aims to provide new options for DSD treatment of DPN in terms of its efficacy and safety. ETHICS AND DISSEMINATION: The review is based solely on a secondary study of published literatures and does not require ethics committee approval. Its conclusion will be disseminated in conference papers, magazines, or peer-reviewed journals. INPLASY REGISTRATION NUMBER: INPLASY202040157.